2000
DOI: 10.1093/hmg/9.20.3065
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of missense mutations at codon 838 in retinal guanylate cyclase correlates with disease severity in patients with autosomal dominant cone-rod dystrophy

Abstract: Three different mutations in codon 838 of GUCY2D, the gene for retinal guanylate cyclase 1, have been linked to autosomal dominant cone-rod dystrophy at the CORD6 locus. To examine the relationship between enzyme activity and disease severity, the three disease-causing substitutions (R838C, R838H and R838S) and four artificial mutations (R838A, R838E, R838L and R838K) were generated. Assay of GCAP1-stimulated cyclase activity in vitro shows that, compared with wild-type, R838E, R838L and R838K possess only low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 21 publications
4
58
0
Order By: Relevance
“…The other published mutations are all clustered at these 4 nucleotide base pairs. Functional studies by Wilkie et al (2000) have shown that base changes at codon 838 (R838A, R838C, R838H and R838S) have altered GCAP1-stimulated cyclase activity. This activity is equal to or superior to wild-type at low Ca2+ concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other published mutations are all clustered at these 4 nucleotide base pairs. Functional studies by Wilkie et al (2000) have shown that base changes at codon 838 (R838A, R838C, R838H and R838S) have altered GCAP1-stimulated cyclase activity. This activity is equal to or superior to wild-type at low Ca2+ concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Variable expressivity is reflected in the extent of macular degeneration observed in individuals from the same family. The relative difference in functional activity observed in different mutants at Arg838 (Wilkie et al, 2000) is likely to be the reason for the difference in disease manifestation. Other cellular and environmental factors might also influence the differences in phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…The mutation in this report, p.R838H, is believed to cause a gain of function increasing the affinity of RetGC-1 for GCAP even in high Ca 2 þ concentrations. 24 The cone photoreceptor death in this disorder is believed to be caused by the high cGMP concentration keeping cGMPgated cation channels open, resulting in increased Ca 2 þ concentration in the cell. 25 Decreasing the cGMP concentration may be therapeutic for these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Y99C may stimulate retGC present in the inner segment (Dizhoor et al, 1994;Liu et al, 1994;Olshevskaya et al, 2002) and open cGMP-gated channels located there (Watanabe and Matthews, 1988). In addition to GCAP1, it is likely that mutations in certain other genes linked to retinal dystrophy in human patients, e.g., retGC1 (Kelsell et al, 1998;Tucker et al, 1999;Wilkie et al, 2000;Ramamurthy et al, 2001) or PDE6b (McLaughlin et al, 1995), or in animal models (for review, see Petersen-Jones, 1998;Chang et al, 2002) also produce photoreceptor degeneration via an increase in Ca 2ϩ . Some other forms of photoreceptor degeneration recently have been associated with a decrease in Ca 2ϩ (Woodruff et al, 2003).…”
Section: Discussionmentioning
confidence: 99%